Pengaruh Penggunaan Media Video Youtube APHD Channel Terhadap Kemampuan Menulis Teks Berita Pada Siswa Kelas VIII Swasta Hkbp Sidikalang Tahun Pembelajaran 2022/2023 - Mega Br. Manullang; Tigor Sitohang; Pontas J. Sitorus; Renita Br Saragih (Journal on Education, 2023)
The success of an education can be achieved with a fun level of learning using media that is able to develop students' learning intentions. This study aims to find out how influential YouTube Video Media is on the Ability to Write News Texts in Grade VIII Students of SMP HKBP Sidikalang in the 2022/2023 Academic Year. This study used a population of 60 and a sample of 30 students in each grade VIII of SMP HKBP Sidikalang in the 2022/2023 academic year. The method used in this study is the quantitative method or also called the discovery method, which determines and analyzes data concretely or empirically, objectively, measurably, rationally and systematically by describing events in the two variables studied. In accordance with this quantitative method which seeks to present data in an ongoing study. Calculation of the hypothesis in this study was tested with the "t" test at a significant level a = 0.05. From the calculated data tcount > table, namely 4.8 > 2.0. Therefore, the null hypothesis (H₂) is rejected and the alternative hypothesis (H₂) is accepted. Thus, it can be concluded that there is an influence of YouTube video media on the ability to write news text in class VIII students of SMP HKBP Sidikalang in the 2022/2023 academic year.